Metafiction in Cien años de soledad: On Melquíades’ Manuscripts - Wahnón, Sultana (2023)
This paper delves into the metafictional character of the Melquíades manuscripts, with the aim of explaining exactly what the interplay of similarities and differences between the novel and the text that doubles it as a speculative tale consists of. Starting from her well-known hypothesis about the Jewish origin of the Buendía family, the author of this work argues, with theoretical and comparative arguments, that the spectacular ending of the novel, in which Aureliano Babilonia discovers the keys to Melquíades and thus gains access to the enigma contained in the manuscripts, is but a prefiguration of the act of reading-interpretation required by the novel itself, itself conceived and executed as an enigmatic and decipherable text. Tacitly polemicising the most recent theories of interpretation, the writer would thus have created the unusual image of a text which, far from being destined for infinite interpretation, would offer the reader the possibility of discovering and revealing its most crucial secrets.